2007
DOI: 10.1074/jbc.m701325200
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids and β2 Agonists Differentially Regulate Rhinovirus-induced Interleukin-6 via Distinct Cis-acting Elements

Abstract: Interleukin-6 (IL-6) is a proinflammatory cytokine up-regulated by rhinovirus infection during acute exacerbations of asthma and chronic obstructive pulmonary disease. The role of IL-6 during exacerbations is unclear; however, it is believed IL-6 could contribute to airway and systemic inflammation. In this study we investigate the effects of common asthma treatments fluticasone propionate and ␤ 2 agonists salmeterol and salbutamol on IL-6 production in BEAS-2B and primary bronchial epithelial cells. Salmetero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
77
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(83 citation statements)
references
References 56 publications
5
77
1
Order By: Relevance
“…We first chose FP at 10 −9  mol/L (1 nmol/L) as this concentration is approximately the EC 50 for these cytokines in bronchial epithelial models (Edwards et al. 2007, 2006), and FP has been found at approximately this concentration in lung tissue following inhalation (Esmailpour et al. 1997).…”
Section: Resultsmentioning
confidence: 99%
“…We first chose FP at 10 −9  mol/L (1 nmol/L) as this concentration is approximately the EC 50 for these cytokines in bronchial epithelial models (Edwards et al. 2007, 2006), and FP has been found at approximately this concentration in lung tissue following inhalation (Esmailpour et al. 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological interventions shown to be relatively successful at preventing asthma exacerbations include inhaled corticosteroids and their combination with long lasting b 2 -agonists (mostly in adults), leukotriene modifiers and anti-immunoglobulin E therapy [8,[94][95][96][97]. Corticosteroids suppress eosinophilic inflammation through various pathways [98,99]. However, the inability of corticosteroids to modulate several other aspects of the immune response to respiratory viruses that lead to asthma exacerbations make them not as effective at preventing or treating virus-induced asthma exacerbations in different age groups [100].…”
Section: Treatmentmentioning
confidence: 99%
“…In pooled clinical trials, fewer cold-related exacerbations occurred with salmeterol/ fluticasone than with fluticasone alone [13]. Further insights into the differences seen in the present analyses have been obtained from in vitro studies, which have shown a dose-dependent reduction in rhinovirus-induced interleukin (IL)-6, IL-8, C-C ligand (CCL)5 (a lymphocyte chemokine) and CXC ligand (CXCL)8 (a neutrophil attractor/activator) when airway epithelial cells were pre-treated with corticosteroids [10,11,32]. Pre-treatment with corticosteroids also abolished rhinovirusinduced loss of b 2 -receptor function [33].…”
mentioning
confidence: 99%
“…Pre-treatment with corticosteroids also abolished rhinovirusinduced loss of b 2 -receptor function [33]. Salmeterol enhanced rhinovirus-induced IL-6 production [11], which may contribute to the adverse effects of LABA monotherapy [34], but salmeterol/fluticasone downregulated CCL5 and CXCL8 mRNA and protein expression at significantly lower concentrations than fluticasone alone, suggesting a synergistic effect [10].…”
mentioning
confidence: 99%
See 1 more Smart Citation